COMMUNITIES AND EXPANSION OF СYCLACHAENA XANTHIIFOLIA PLANTS IN ANTHROPOGENICALLY DISTURBED ECOTOPES - Курдюкова, О. М.; Жердєва, К. О. (Scientific Progress & Innovations, 2015)
This paper contains the data obtained in the long-term studies of the features which characterize the growth and development of Сyclachaena xanthiifolia plants, as well as species and quantitative composition of associated weeds in various age-related cenopopulations with different ecologo-phytocenotic and anthropogenic influencing factors. It is determined, that the species and quantitative composition of the most common weeds in uneven-aged communities of Сyclachaena xanthiifolia plants was considerably varied, and the intensity of plant populations from emerging to maturity was decreased by about 10 times. The maximum intensity of emerging Сyclachaena xanthiifolia plants (412–321 pieces/m2), vital power level (4), and seed growing potential (80,5–93,8 thousand of seeds per plant) are characteristic for cenopopulations with a low anthropogenic impact, which are located within territories of livestock farms and along river banks with loose humid soils which are rich with organic substances.